Optimizing Resource Utilization in Wireless Multimedia Networks - Bahl, Victor; Chlamtac, Imrich; Farago, Andras (Institute of Electrical and Electronics Engineers, Inc., 1997)
The task of supporting integrated multi-rate multimedia traffic in a bandwidth poor wireless environment poses a unique and challenging problem for network managers. In this paper we propose a novel bandwidth allocation strategy which partitions the available bandwidth amongst the different traffic classes in a manner that ensures quality of service (QoS) guarantees for digital video while minimizing the maximum blocking probability for voice and data connections. At the connection level, optimum utilization of the reserved bandwidth is achieved through intra-frame statistical multiplexing, while at the system-level, the delicate task of partitioning the bandwidth is accomplished by developing an efficient algorithm which uses traffic parameters consisting only of aggregate traffic load and the total available bandwidth. The algorithm built on non-trivial mathematical results, is simple, robust, and well suited for practical implementations.